ANALYSIS OF TIGHT GAS RESERVOIRS AND LITHOLOGICAL-PETROPHYSICAL ASSESSMENT OF UPPER AND MIDDLE CARBONIFEROUS STRATA OF SVYATOGORSKA AREA - Oliinyk, O.; Antoniuk, V.; Bezrodna, I.; Vyzhva, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper concerns the analysis of the world practice in the study of tight gas reservoirs and some of their lithological and petrophysical properties are demonstrated on the example of Svyatogorska Area perspective intervals. The purpose of this work is to establish the features of petrophysical properties of tight gas reservoirs from the upper and middle Carboniferous strata of Svyatogorska area according to laboratory and well logging data and matching the obtained geophysical results with lithological composition and mineral structure of rocks to assess gas prospects. The laboratory investigation on core samples included petrographic and petrophysical analysis of rocks. The effective porosity cutoff value for tight gas reservoirs of the studied area is 4,5 % under reservoir conditions and 4 % in the laboratory settings. 130 core samples were selected, for which the effective porosity is larger than the cutoff value. The histogram of effective porosity and absolute permeability distribution for tight gas intervals shows that PHI is in the range of 4–7 % and K – 0.01–2 mD (the largest number of samples has K – 0.01 mD). Conducted analysis of the micropetrographic study results of the core material showed that the matrix of the Moscowian stage rocks takes an average of 70 % from the volume, represented by 41-47 % quartz, 3 - 10.5 % – feldspar and 2.1–6 % – mica minerals. Cement is represented mainly by illite clay component (14–17.5 %) with calcite content (3–8.75 %). According to the formation evaluation of the well logging data clay volume, effective porosity and gas saturation were calculated for the well №10 Svyatogorska area. The intervals: 3836.4–3866.6 m and 4107.6–4140,4 4 m were indicated as tight gas reservoirs. The effective porosity of promising formations varies in the range - 4.5–9.5 %, and the gas saturation in 50–65 %. According to the results of well testing – 19.0 thousand m3/d flow rate of gas was obtained in the interval 4042–4150 m of the well № 10 (before intensification). Summarizing the obtained results and comparing with the world oil and gas practices in the field of unconventional sources of hydrocarbons one suggests that the rocks of the Moscow strata of Svyatogorska Area are tight gas reservoirs.